Electrochemical performance of binder-free NiO-PANI on etched carbon cloth as active electrode material for supercapacitor - Razali, Shaifulazuar; Majid, Siti Rohana (Elsevier, 2018)
Binder free electrode for supercapacitor application was successfully fabricated which consists of carbon cloth‑nickel oxide-polyaniline (EC-NiP). The composite electrode was prepared by growing NiO on EC via hydrothermal followed by the electrodeposition of PANI. The crystallite sizes of NiO were varied from 5.73 nm to 17.81 nm over the temperature range of 200 to 500 °C. The optimized electrode, heated at 300 °C (NIP300) showed good specific capacitance of 192.31 Fg−1 with energy density of 21.63 mWhkg−1 and 4.81 Wkg−1 of power density at 0.5 Ag−1 current density in 0.5 M H2SO4 electrolyte. The symmetrical NIP300//PVA + 0.5 M H2SO4//NIP300 cell exhibit excellent reversibility where the specific capacitance retained 72% of the initial value after 4500 cycles.